Proceedings of the Conference on Continuous Advances in QCD 2004 : William I. Fine Theoretical Physics Institute, Minneapolis, USA, 13-16 May, 2004 - Gherghetta, T. (World Scientific, 2004)
This book contains articles on the latest research in QCD from some of the leading experts in the field. These are based on talks presented at the Continuous Advances in QCD 2004 workshop held at the William I Fine Theoretical Physics Institute. The book will be a useful reference source for graduate students and researchers in high energy physics. The proceedings have been selected for coverage in:. Index to Scientific & Technical Proceedings® (ISTP® / ISI Proceedings). Index to Scientific & Technical Proceedings (ISTP CDROM version / ISI Proceedings). CC Proceedings - Engineering & Phy.